URGENSI SUPERVISI PENDIDIKAN PERSPEKTIF Q.S. ALI IMRAN: 29 DAN QS. AL-ISRA’: 84 - Tazkiyah, I'anatut; Kiptiyah, Arofatul; Abidin, Munirul; Hamidah, Tutik; Nasrulloh (LPPM STAI Muhammadiyah Probolinggo, 2023)
Supervision is often considered scary by employees or teachers. In fact, there is important supervision in an institution, including Islamic educational institutions so that they can be assessed and evaluated for the better in accordance with their standards. The study aims to examine more deeply to determine the urgency of educational supervision based on the interpretation of Q.S. Ali Imran: 29 and Q.S Al-Isra': 84. This type of research is descriptive qualitative with a literature study approach, with the main data source of the Quran, and is supported by books, books, articles and websites. Data analysis techniques with reduction, data models and conclusions. The result of this study is that the urgency of educational supervision is indeed important because Allah alone in supervising his creatures has been explained in Q.S Ali Imran: 29 and Al-Isra': 84, there is supervision for assessment and giving proper reply to creatures, but in the context of institutions in the world for the work efforts of employees and teachers (educational institutions), as well as the function of supervisors as people who are more experienced in assessing is also important for evaluation and measuring the extent to which standards that have been met.